GROWTH OF SEED INDUSTRY IN INDIA VIS-À-VIS TELANGANA - P. RADHIKA; D. SRINIVASA CHARY, S. KAVI RAJU, A. JANAIAH, R. VIJAYA KUMARI (The Journal of Research, PJTSAU, 2023)
This paper examines the trends in growth of seed industry in India and Telangana with special focus on rice seed sector. The compound annual growth rate (CAGR) method was used to estimate the growth in distribution of certified seeds of important crops with special focus on certified seed of rice. While, the size of seed business computed for two different points of time 2014 and 2020 to understand the relative importance of Telangana in Indian seed industry. The size of global seed business increased by about 15 per cent between 2012 and 2020. Subsequently, the India’s share in global seed business has increased from about 4 to 6 per cent during the same period. On other hand, the relative share of Telangana in the Indian seed business has declined from about 30 to 19 per cent between 2014 and 2020 respectively. The reason for this change is a sizeable portion of seed industry being shifted to other neighbouring states specially in case of hybrid rice and Bt cotton seed production. The distribution of certified seed of all crops in India and the state of Telangana has shown a positive compound annual growth rate over the past 20 years, with deceleration in growth rates in recent period. The relative shares of seed production area under hybrid rice and BT cotton hybrids to total area under seed production in Telangana declined from about 23.3 to 13.3 per cent and 8 to 4.75 per cent respectively between 2014 and 2020. However, total area under seed production for all crops and seed growers increased substantially in the state between this period. Hence, the seed growers in Telangana state may be provided with the required incentives along with formulation of a comprehensive seed production policy for further promotion of seed industry.